Impact of Solar and Wind Prices on the Integrated Global Electricity Spot and Options Markets: A Time Series Analysis - Alsaedi, Yasir; Tularam, Gurudeo Anand; Wong, Victor (International Journal of Energy Economics and Policy, 2020)
Following the liberalisation of the global electricity markets, spot and options markets have been established in many countries. Electricity pricing issues, coupled with increased concern regarding global warming and the greenhouse effect, represent the driving factors behind electricity price movements. Australia, Germany, the United States (US) and other countries worldwide have increasingly shifted their focus away from fossil fuels and towards energy generated from renewable sources, including solar and wind power. This paper examines the behaviour of the Australian, German and US electricity markets in terms of the impact of solar and wind pricing on the electricity spot and options markets for the period January 2006 to March 2018. Using a vector autoregression analysis, we examine both the direction of influence and the influence absorption through Granger causality testing, the impulse response function and forecast error variance decompositions. Our findings indicate that the electricity markets in Australia, Germany and the US are interdependent and related with regards to solar and wind price changes, meaning that the investigated electricity markets are influenced by movements in other electricity markets. The findings of this study are important for investors, energy analysts, government organisations and policymakers. Keywords: Electricity pricing, Renewable energy, VAR model. JEL Classifications: C32, Q41, Q42 DOI: https://doi.org/10.32479/ijeep.8939